Yoga as a potential psychosocial tool: Results from a quasi-experimental single-arm study on victims of flood affected state of Kerala. Issue 3 (September 2021) - Mathew, D.
Abstract: Objectives: Mental and social health is among the notable domains affected by natural disasters, with nearly one-quarter of the people living in an area affected by natural disasters expressing the symptoms of depression, anxiety, post-traumatic stress disorder, bipolar disorder, or schizophrenia. Bringing harmony among these affected individuals is an important clinical priority. The effect of yoga, which is reported to reduce mental disorders to a great extent in many conditions, has not been studied in the setting of natural disaster recovery. Methods: Thirty-two participants [Mean age 37.8(SD ± 8.9)] from a flood-affected state of India exhibiting mental and social impacts from the natural disaster were enrolled for 15 days of yoga interventions after obtaining written consent. Breathing exercises and guided relaxation techniques were provided as intervention after obtaining a self-rated visual analog scale (VAS) for fear, sadness, anxiety, and lack of sleep. Results: All participants completed the study. Statistically significant changes were observed (P<0.05) in all the VAS dependent scale variables such as fear, sadness, anxiety, and lack of sleep. No adverse events were reported. Conclusion: Fifteen days of yoga interventions in victims of the flood-affected region might offer resilience to the people affected by natural disasters. Results of this study are encouraging and yoga can be introduced for addressing mental health issues in such emergencies and can be a valuable tool. However, more studies with robust designs and focused tools to determine the effects are warranted. Highlights: Yoga, a pearl of ancient wisdom is known to produce favorable clinicaloutcomes through its mind-body practices. Yoga interventions are used to treat depression, anxiety, and other mental health disorders. Yoga can be utilized as a psychosocial tool to mitigate mental traumas during natural emergencies. Yoga interventions are received well by the victims of natural disasters.